(untitled) (International Journal of Engineering and Computer Science, 2015)
The increasing industrialization and motorization of the world has led to a steep rise for the demand of petroleum products. Petroleum based fuels are obtained from limited reserves. These finite reserves are highly concentrated in certain regions of the world. Therefore, those countries not having these resources are facing a foreign exchange crisis, mainly due to the import of crude oil. Hence, it is necessary to look for alternative fuels, which can be produced from materials available within the country. Biodiesel can be extracted from vegetable oils and waste fats. The present work examined the use of a Tamanu oil, a new possible source of alternative fuel for direct injection diesel engine. The biodiesel has been prepared from Tamanu oil by Trans-Esterification method .Diesel and Tamanu oil methyl ester (B15, B25, B50, B100) fuel blends are used for conducting the performance and emission in terms of 20% load increments from no load to full load. From the experiments it is found that Tamanu oil is a better NOx reduction fuel.